Crosstalk between p53 and mitochondrial metabolism - Itahana, K.; Pervaiz, Shazib (Springer Netherlands, 2014)
© 2014 Springer Science+Business Media Dordrecht. All rights are reserved.After being obtained from bacteria, eukaryotic mitochondria acquired a myriad of metabolic functions during evolution to coordinate energy efficiency and demand with host cells during cell proliferation and growth arrest for maintaining cellular homeostasis as well as functions in decisions of cell death and survival. To achieve this, mitochondria and host cells have developed tight communications, and recent evidence suggests that tumour suppressor p53 actively participates in these communications. p53 influences mitochondrial metabolism by activating or repressing the transcription of target genes as well as directly interacting with proteins in different cellular compartments, including mitochondria. This review discusses recent findings of p53-mediated regulation of cellular metabolism, such as oxidative phosphorylation, glutamine and fatty acid metabolism, autophagy, glycolysis, and reactive oxygen species, to better understand the tumour suppressive functions of p53, which may facilitate the identification of novel therapeutic targets and strategies.